A critical study on the degree of the statutory rape punishment in Malaysia / Nurliyana Mohd Jafri … [et al.] - Mohd Jafri, Nurliyana; Mawan, Christhoper Enteri; Mohd Radzif, Nurul Syazreen; Zabarudin, Mohd Nazreen (2014)
This research paper is mainly discussing on the issue of statutory rape as governed under Section 375 (g) and Section 376 (2) (d) and (e) of the Penal Code. The aims of this research paper are to study on the degree of the statutory rape punishment and whether a higher sentence on statutory rape offences should be imposed plus an examine on how it can be implemented in order to curb statutory rape cases in Malaysia. Section 376 (2) (d) and (e) of the Penal Code provides that whoever rapes a woman when she is below twelve years old or is below sixteen years old, shall be imprisoned for a minimum of five years and up to a maximum of thirty years and shall also be liable to whipping. However, the lack of stringency of the sentence for statutory rape has made this crime to be at a worrying state in Malaysia. Thus, there are several suggestions proposed in curbing this problem. Firstly, the minimum term of imprisonment for statutory rapist should be increased to 10 years instead of 5 years. Secondly, a Sentencing Council should be established based on a model from United Kingdom. Thirdly, Section 294 of the Criminal Procedure Code should be amended to exclude good behaviour bond from being granted to first-time and youthful offender. Next is amendment towards Section 293 of the Criminal Procedure Code to make public caning as a mandatory punishment. Lastly, statutory rape offenders should be registered as a sex offender.